ANTAGONIST’S DOUBLE PERSONALITY IN SHARON SALA’S NOVEL COLD HEART - Anna Syafridah; Asnani Asnani (Universitas Islam Sumatera Utara, 2020)
Double personality usually occurs in someone who has experienced trauma in past. Double personality should not happen in someone’s life. The traumatic event can impact their life. This study is conducted to analyze double personality reflected in the novel Cold Heart and to find out the causes of the antagonist’s double personality. This research uses descriptive qualitative method because the process of the result and discussion are accomplished descriptively. The descriptive qualitative methodology is applied to explain the antagonist’s double personality from the text in the novel. The result of this research shows that the antagonist’s in the novel has two different personalities. They are being obsessed with women and being kind to women. These personalities are really opposite. Then, there are two causes which result in the antagonist’s double personality. The first is his brother’s death and the second is being a cause of a murderer. Both events make the antagonist feel traumatic. Consequently, he has such double personality.